Kinerja Manajerial : Hasil Kerjasama Tim dan Perbaikan Berkesinambungan - Hastuti, Sri; Wijayanti, Luky (Jurnal Riset Ekonomi dan Bisnis, 2009)
The environment which dynamic and complex, PT. PLN ( Persero) of Distribution of East Java of APJ South Surabaya need the decision making which quickly, flexible approach, work base on knowledge and intensive process. The condition require the very high worker involvement in organization through the team forming. The description have an intention to know empirically is influence of team cooperation to managerial performance and continual repair influence to managerial performance at PT. PLN (Persero) of Distribution of East Java of APJ South Surabaya.The object which used is assistant of laboring and supervisor manager at PT. PLN (Persero) of Distribution of East Java of APJ South Surabaya. The proving the analysis used its analysis model that is multiple regression.The result of research and hypothesis examination obtained are the influence of team cooperation and continually repair to managerial performance.Keywords: Team Cooperation, Repair Continually, Managerial Performance